A Review of Relationships Between Wood Quality and Silvicultural Practices - Tomy Listyanto; John Doland Nichols (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
The effect of silviculture on wood quality has been approached from different perspectives. This relationship is being a critical concern of forest managers, landowners, and also researchers. Reliable information is needed to support forest managers in predicting the consequences of various silvicultural practices in terms of quantity and wood quality.Wood has beed used for a variety of products. Each product has particular requirements regarding quality. The variation of wood quality requirement allows industries to decide to use timber resource appropriate for their products. Silvicultural practives cover all treatments applied in forest stand management especially to improve the quality of stand, including manipulation of the availability of sunlight, nutrient and water by using several treatments such as thinning, control of spacing, fertilizing, and pruning. The quality of stand is aimed to achieve particular forest management objectives including higher wood quality.There is no broad generalization regarding the relation between silvicultural practice and wood quality. Many investigators showed positive results in relation to producing high quality of wood products, while other researchers revealed negative effects. Reliable information is needed to support forest managers in predicting the consequences of various silvicultural practices in relation to the wood quantity and quality. Continuous research is needed to find methods of producing wood of high quality based on silvicultural practices and genetic improvement which can be used in wider area by considering limitation including environment and geographic variation.